2018
DOI: 10.1186/s12974-018-1350-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related deregulation of TDP-43 after stroke enhances NF-κB-mediated inflammation and neuronal damage

Abstract: BackgroundTDP-43 has been identified as a disease-associated protein in several chronic neurodegenerative disorders and increasing evidence suggests its potentially pathogenic role following brain injuries. Normally expressed in nucleus, under pathological conditions TDP-43 forms cytoplasmic ubiquitinated inclusions in which it is abnormally phosphorylated and cleaved to generate a 35 and a 25 kDa C-terminal fragments. In the present study, we investigated age-related expression patterns of TDP-43 in neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 47 publications
4
39
0
Order By: Relevance
“…There are therefore clinical and experimental data suggesting a bidirectional relationship between cerebral vascular dysfunction and pathological tau. There is evidence from recent studies that TDP-43 pathology, likewise, is associated with cerebral vascular dysfunction, including pericyte loss and small vessel disease [ 114 , 115 ]. Lastly, cerebral ischaemia induces phosphorylation of α-synuclein at serine-129; this is the predominant disease-related modification of α-synuclein in Lewy bodies and neurites in Parkinson disease, and dementia with Lewy bodies, and also is significantly associated with concomitant AD pathology in these Lewy body diseases [ 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are therefore clinical and experimental data suggesting a bidirectional relationship between cerebral vascular dysfunction and pathological tau. There is evidence from recent studies that TDP-43 pathology, likewise, is associated with cerebral vascular dysfunction, including pericyte loss and small vessel disease [ 114 , 115 ]. Lastly, cerebral ischaemia induces phosphorylation of α-synuclein at serine-129; this is the predominant disease-related modification of α-synuclein in Lewy bodies and neurites in Parkinson disease, and dementia with Lewy bodies, and also is significantly associated with concomitant AD pathology in these Lewy body diseases [ 116 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an animal study showed that injection of pre-formed α-syn fibrils triggered reactive microgliosis prior to nigral degeneration [81,82]. The level of cytoplasmic TDP-43 increases with age, and it was suggested that TDP-43 is a modulator of inflammation, which activates the nuclear factor kappa-light-chain-enhancer of activated B cells pathways, leading to a deregulation of innate immune response [83].…”
Section: Neurodegeneration-induced Neuroinflammation Chronic Inflammmentioning
confidence: 99%
“…Thus far, our data suggested that low-grade systemic inflammation can promote TDP-43-induced neurodegeneration, resulting in cognitive impairment. Given that the deregulation of TDP-43 can induce neuroinflammation and increase neuronal death through NF-κB signaling [28,44], we decided to explore whether the observed effects were due to alterations in the NF-κB pathway. Our biochemical analysis demonstrated no changes in phosphorylation of NF-κB p65 or IKβα degradation within the confines of our study design (data not shown).…”
Section: Tdp-43 Overexpression Induces Astrogliosis and Microgliosismentioning
confidence: 99%